Heart Failure Medication Therapy Adherence Clinic (HF-MTAC) training 2024 / Nur Syazwani Taridi and Nurulfalahin Daud @ Ibrahim - Taridi, Nur Syazwani; Daud @ Ibrahim, Nurulfalahin (Faculty of Pharmacy, 2024)
Heart failure (HF) is a clinical syndrome associated with recurrent hospitalisations and high mortality. Poor adherence to drug therapy is a major problem which requires involvement of pharmacists to achieve desired therapeutic outcome among HF patients. As such, Heart Failure Medication Therapy Adherence Clinic (HFMTAC), an ambulatory care service is initiated, which is conducted by pharmacists in collaboration with other healthcare providers with the aim to improve patient care in the realm of HF management. In the early last September, two pharmacy lecturers from our Faculty of Pharmacy, Madam Nur Syazwani Taridi and Ms. Nurulfalahin Daud @ Ibrahim had an opportunity to undergo a 2-weeks HF-MTAC training at Sultan Idris Shah Hospital (HSIS) Heart Center in Serdang, Selangor from 2nd until 13th of September 2024. The objectives of this training are to grasp the recent HF pharmacotherapy updates and to acquire an extensive clinical training which will have a great benefit for future teaching and learning sessions.